2013
DOI: 10.1590/s0004-27302013000600004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased astrocytic GFAP expression in streptozotocin-induced diabetes after gliotoxic lesion in the rat brainstem

Abstract: Objective: The aim of this study was to evaluate the effect of diabetic hyperglycemia on astrocyte function, estimated by means of glial fibrillary acidic protein -GFAP -immunohistochemical expression. Materials and methods: Adult male rats received a single intravenous injection of streptozotocin (50 mg/kg) and were submitted 10 days later to a single injection of 10 microlitres 0.1% EB solution or 0.9% saline solution into the cisterna pontis. Ten microliters of 0.1% EB or 0.9% saline solution were also inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Diabetic rats presented lesions similar to those observed in earlier investigations (13)(14)(15)24) involving EB injection in streptozotocin-induced diabetes and comparable to those observed in cyclophosphamide immunosuppressed rats (5), in which large amounts of myelin debris and demyelinated axons were found as well as delayed remyelination by both oligodendrocytes and Schwann cells. The persistence of myelin-derived membranes in an expanded extracellular space suggested that somehow phagocytic activity was impaired (13).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Diabetic rats presented lesions similar to those observed in earlier investigations (13)(14)(15)24) involving EB injection in streptozotocin-induced diabetes and comparable to those observed in cyclophosphamide immunosuppressed rats (5), in which large amounts of myelin debris and demyelinated axons were found as well as delayed remyelination by both oligodendrocytes and Schwann cells. The persistence of myelin-derived membranes in an expanded extracellular space suggested that somehow phagocytic activity was impaired (13).…”
Section: Discussionsupporting
confidence: 84%
“…The EB-induced lesions were similar to those previously described in the brainstem of diabetic (13)(14)(15) and non-diabetic rats (1)(2)(3)(4)(5)(6). In general terms, they were characterized by demyelinated areas in the ventral surface of the pons and mesencephalon, con-taining in the central region phagocytic cells, variable amounts of myelin-derived membranes in a distended extracellular space as well as naked axons.…”
Section: General Aspects From Eb-induced Lesionssupporting
confidence: 81%
See 2 more Smart Citations
“…How-ever, it is reported that apparent decreased GFAP content reflects a decrease in GFAP expression, but may not be a decrease in the number of astrocytes [62].…”
Section: Discussionmentioning
confidence: 99%